2023
DOI: 10.1177/19458924231204129
|View full text |Cite
|
Sign up to set email alerts
|

Race and Area of Deprivation Index Predict Outcomes of Endoscopic Sinus Surgery for Chronic Sinusitis

Firas Hentati,
Jaehee Kim,
David Hoying
et al.

Abstract: Objective The purpose of this study is to characterize the presentation, outcomes, and barriers to care for White and non-White patients undergoing endoscopic sinus surgery (ESS). Background ESS is often successful in providing long-term relief for patients suffering from chronic rhinosinusitis (CRS). Literature that uses robust measures of socioeconomic status (SES) and barriers to care to assess ESS outcomes is limited. Methods A retrospective matched cohort study of patients who underwent ESS for CRS betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Hentati and colleagues conducted a retrospective matched cohort study analyzing the impact of race and socioeconomic status on presentation and outcomes in patients with chronic rhinosinusitis (CRS) undergoing endoscopic sinus surgery. 1 They found that nonwhite patients have worse outcomes, higher revision rates, less consistent follow up, and present from areas with fewer resources compared to white patients. Therefore, acknowledging the socioeconomic status is essential when treating patients with CRS in order to mitigate disparity-related outcomes.…”
mentioning
confidence: 99%
“…Hentati and colleagues conducted a retrospective matched cohort study analyzing the impact of race and socioeconomic status on presentation and outcomes in patients with chronic rhinosinusitis (CRS) undergoing endoscopic sinus surgery. 1 They found that nonwhite patients have worse outcomes, higher revision rates, less consistent follow up, and present from areas with fewer resources compared to white patients. Therefore, acknowledging the socioeconomic status is essential when treating patients with CRS in order to mitigate disparity-related outcomes.…”
mentioning
confidence: 99%